PENERAPAN PENDEKATAN PRAGMATIK (PRINSIP-PRINSIP PENGGUNAAN BAHASA) DISERTAI TEKNIK KOREKSI SESAMA TEMANDAN KOREKSI OLEH GURU UNTUK MENINGKATKAN KETERAMPILAN MENCERITAKAN PENGALAMAN PADA SISWA KELAS VIIE SMP NEGERI 5 NEGARA - I Putu Mas Dewantara (Jurnal Santiaji Pendidikan (JSP), 2013)
This research was intended to (1) describe the development of telling experience skill of the students of class VII E SMP Negeri 5 Negara through the implementation of pragmatic approach (principles of language use) accompanied by pair correction technique and correction by Teacher, (2) describe the steps of learning and teaching activities in the implementation of pragmatic approach (principles of language use) accompanied by pair correction technique and correction by Teacher to develop the skill of telling experiences by the students of VII E SMP Negeri 5 Negara, and (3) describe students’ response about the implementation of pragmatic approach (principles of language use) accompanied by pair correction technique and correction by teacher. The subjects of this research were students and teacher of bahasa Indonesia in SMP Negeri 5 Negara. This research used the two-cycle classroom action research. The data about the skill of telling experiences was gathered through test method analyzed by qualitative description method. The data about students’ response was gathered through questionnaire method analyzed by qualitative description and quantitative description. The result of the research showed that the implementation of pragmatic approach (principles of language use) accompanied by pair correction technique and correction by teacher can (1) develop the skill of telling experience by students, (2) be done through 19 appropriate learning steps, and (3) develop students’ positive response in telling experience. Bahasa Indonesia’s teachers is hoped to implement the pragmatic approach (principles of language use) accompanied by pair correction technique and correction by teacher to develop the skill of telling students’ experiences that make the teaching-learning activity can run conducive, creative, and innovative.